Titanium Ions Release from an Innovative Titanium-Magnesium Composite: an in Vitro Study - Zlatko Stanec; Jasna Halambek; Krešimir Maldini; Martin Balog; Peter Križik; Zdravko Schauperl; Amir Ćatić (University of Zagreb. School of Dental Medicine, 2016)
The innovative titanium-magnesium composite (Ti-Mg) was produced by powder metallurgy (P/M) method and is characterized in terms of corrosion behavior. Material and methods: Two groups of experimental material, 1 mass% (Ti-1Mg) and 2 mass% (Ti-2Mg) of magnesium in titanium matrix, were tested and compared to commercially pure titanium (CP Ti). Immersion test and chemical analysis of four solutions: artificial saliva; artificial saliva pH 4; artificial saliva with fluoride and Hank balanced salt solution were performed after 42 days of immersion, using inductively coupled plasma mass spectrometry (ICP-MS) to detect the amount of released titanium ions (Ti). SEM and EDS analysis were used for surface characterization. Results: The difference between the results from different test solutions was assessed by ANOVA and Newman-Keuls test at p<0.05. The influence of predictor variables was found by multiple regression analysis. The results of the present study revealed a low corrosion rate of titanium from the experimental Ti-Mg group. Up to 46 and 23 times lower dissolution of Ti from Ti-1Mg and Ti-2Mg, respectively was observed compared to the control group. Among the tested solutions, artificial saliva with fluorides exhibited the highest corrosion effect on all specimens tested. SEM micrographs showed preserved dual phase surface structure and EDS analysis suggested a favorable surface bioactivity. Conclusion: In conclusion, Ti-Mg produced by P/M as a material with better corrosion properties when compared to CP Ti is suggested.